Adolescent angst: enrollment on clinical trials - Keegan, Theresa H M; Parsons, Helen M (Hematology, 2018)
Survival among adolescents and young adults (AYAs) ages 15 to 39 with cancer has not improved to the same extent as that of pediatric and older adult cancer patients, which is thought to relate, in part, to the lower participation of AYAs in clinical trials. Because significant efforts have been made to improve clinical trial enrollment for AYAs, we (1) present contemporary clinical trial enrollment rates by cancer type, sociodemographic characteristics, and treatment setting and (2) discuss provider-, patient-, and system-level barriers to clinical trial participation. Contemporary studies examining clinical trial enrollment among AYAs have continued to find low overall participation relative to pediatric populations, with most studies observing no significant improvements in enrollment over time. In addition to age and cancer type, enrollment varies by treatment setting, health insurance, and race/ethnicity. Access to available clinical trials may be increased by appropriate referral of AYAs to pediatric and adult specialty cancer centers with studies relevant to the AYA population because most AYAs are treated in the community setting. Even with similar access to trials, however, AYAs may be less likely to participate, and therefore, future efforts should focus on better understanding and addressing barriers to enrollment as well as improving education and outreach regarding clinical trials.